Modelling of elastoviscoplastic properties of the subgrade. Problem statement 1 - V. M. Bel’Kov (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
A brief analysis of the physical and mechanical properties of materials, used in the construction of the rail bed, has shown that in scientific and technical literature there is scattered unsystematic information obtained under different physical conditions for bulk materials (gravel and sand). Unstructured data on the physical and mechanical properties of granular materials does not allow formulating a relatively complete dynamic theory for a wide range of static and dynamic loads, vibration acceleration and humidity conditions in relation to rail transport. In this article the authors formulate the problem of stability of the system “clayey soils in the main area - protective layer of sand cushions - ballast crushed stone prism” under the impact of harmonic oscillations on the basis of physico-chemical mechanics. Loam or clay belongs to isotropic visco-plastic media, sand and gravel - to disperse granular media. Filling the pore space of the gravel with weeds leads to the retention of precipitation and melt liquid. During deflation processes clogging of the gravel layer is increased. Despite the enormous practical value, properties of granular materials, until recently, practically not been studied. Under appropriate conditions this material may behave as a solid and as liquid and as gas. Each phase has unique properties that distinguish granular materials from all other substances. If the vibration field is applied to layer of gravel or sand, the energy of this motion is passed even through individual granules. As a result, with sufficiently high amplitude of jitter a phase transition occurs: the entire mass of granular material gets in motion, begins to flow due to reduction in friction between the particles and behaves as a kind of “granular liquid”. Fluid state of gravel stone occurs at much large values of the amplitude of vibration because of its angular shape. The result is a hydrodynamic instability, then convection starts and the vortices spontaneously appear.